Networked multisensor decision and estimation fusion : based on advanced mathematical methods - Zhu, Yunmin, 1944- (Boca Raton, Fla. : CRC Press, 2013)
"Multisource information fusion has become a crucial technique in areas such as sensor networks, space technology, air traffic control, military engineering, communications, industrial control, agriculture, and environmental engineering. Exploring recent signficant results, this book presents essential mathematical descriptions and methods for multisensory decision and estimation fusion. It covers general adapted methods and systematic results, includes computer experiments to support the theoretical results, and fixes several popular but incorrect results in the field"--
1. Introduction -- 2. Parallel statistical binary decision fusion -- 3. General network statistical decision fusion -- 4. Some uncertain decision combinations -- 5. Convex linear estimation fusion -- 6. Kalman filtering fusion -- 7. Robust estimation fusion.
Includes bibliographical references and index.
Also available as an electronic resource.
Keywords: Sensor networks; Multisensor data fusion -- Mathematics